Improving Students Reading Ability by using Guided Reading Procedure (GRP) at Elementary School - Rindu Kaya Sinambela; Kammer Tuahman Sipayung (Jurnal Scientia, 2023)
Reading is an activity done to get message to conveyed by the author through the medium of words or standard language. The objective of this study to improve the reading ability through guided reading procedure on students grade six at Elementary School Rambah Serit. The design of this research is classroom action research. The students at grade six twenty students is the subject of this research. One of the abilities that students must have is ability reading, with the aim that students understand the contents of the reading text which he has read. However, there are still many students who are less able to read English. To improve students' reading skills, the guide reading method is applied. After applying the guide reading method I with the pre-reading stage, reading stage, and post-reading stage. In learning, results are obtained sixth grade students' reading ability. Cycle I obtained students' English reading ability of 20%, cycle II students' reading ability experienced an increase in students' reading English to 60%. It can be concluded that learning using the guide reading method can improve reading comprehension skills of sixth grade elementary school students.